2011
DOI: 10.1021/jp208488z
|View full text |Cite
|
Sign up to set email alerts
|

Solid/Liquid Phase Diagram of the Ammonium Sulfate/Maleic Acid/Water System

Abstract: We have studied the low temperature phase diagram and water activities of the ammonium sulfate/maleic acid/water system using differential scanning calorimetry and infrared spectroscopy of thin films. Using the results from our experiments, we have mapped the solid/liquid ternary phase diagram, determined the water activities based on the freezing point depression, and determined the ice/maleic acid phase boundary as well as the ternary eutectic composition and temperature. We also compare our results to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…We have studied five dicarboxylic acid/(NH 4 ) 2 SO 4 /H 2 O ternary systems in our lab: C 3 H 4 O 4 /(NH 4 ) 2 SO 4 /H 2 O, C 4 H 4 O 4 /(NH 4 ) 2 SO 4 /H 2 O, C 4 H 6 O 5 /(NH 4 ) 2 SO 4 /H 2 O, C 5 H 8 O 4 /(NH 4 ) 2 SO 4 /H 2 O, and C 4 H 6 O 4 /(NH 4 ) 2 SO 4 /H 2 O studied in this paper. Table summarizes some of the key physical properties that we measured in these systems.…”
Section: Resultsmentioning
confidence: 99%
“…We have studied five dicarboxylic acid/(NH 4 ) 2 SO 4 /H 2 O ternary systems in our lab: C 3 H 4 O 4 /(NH 4 ) 2 SO 4 /H 2 O, C 4 H 4 O 4 /(NH 4 ) 2 SO 4 /H 2 O, C 4 H 6 O 5 /(NH 4 ) 2 SO 4 /H 2 O, C 5 H 8 O 4 /(NH 4 ) 2 SO 4 /H 2 O, and C 4 H 6 O 4 /(NH 4 ) 2 SO 4 /H 2 O studied in this paper. Table summarizes some of the key physical properties that we measured in these systems.…”
Section: Resultsmentioning
confidence: 99%
“…In a study of growth factor of hygroscopic acids such as malonic acid, citric acid, and malic acid, Peng et al found that these water-soluble organic acids at low concentrations contribute less than inorganics to the hygroscopicity of atmospheric aerosols. Extended to ternary systems, Beyer et al and Pearson and Beyer studied thermodynamic properties of dicarboxylic acids/ammonium sulfate/water mixtures using differential scanning calorimetry and infrared spectroscopy of thin films. They have reported water activities and solid/liquid ternary phase diagrams for systems having dicarboxylic acids like malonic, glutaric, maleic, and succinic acids below 300 K. Bilde et al have reviewed experimental measurements of equilibrium vapor pressures from evaporation rate of straight-chain dicarboxylic acids with water and inorganics.…”
Section: Introductionmentioning
confidence: 99%
“…Given the abundance and importance of organic acids in atmospheric aerosols, measurements and models of thermodynamic properties of the organic species in solution are essential for accurate predictions of the gas/particle partitioning and aerosol size distribution and composition . Experimental thermodynamic studies include investigations into vapor pressure measurements and hygroscopic properties. Soonsin et al reported that organic acids with an even number of carbon molecules (“even acids”, e.g., succinic acid) are less soluble in water and have lower vapor pressures than odd acids. In a study of growth factor of hygroscopic acids such as malonic acid, citric acid, and malic acid, Peng et al found that these water-soluble organic acids at low concentrations contribute less than inorganics to the hygroscopicity of atmospheric aerosols.…”
Section: Introductionmentioning
confidence: 99%